Space for the Nervous Tissue: Instead of introduction - Lidin, Konstantin (project baikal, 2015)
A university campus is not only a complex of living, education and auxiliary facilities. It is a certain style of life. It is developed to fulfill a certain task: knowledge preservation and generation. The system of preservation and processing of the society’s knowledge has functions similar to the nervous system. The stronger the society’s scientific and academic network is, the more intellectual, advanced, diverse and flexible is the society’s response to extrinsic stimuli. The nervous system of present day states is similar to the nervous system of insects – with ganglions and different sense organs. A university campus is an elaborate complex of “sense organs” (research laboratories) and “ganglions” (theoretic groups, seminars etc.). The nervous tissue is the most delicate and volatile of all tissues in the organism. Under nutritional deficiency, too strong or too light external effects, the nervous system fails. Its signals malfunction, and either neuralgia or anesthesia occurs. If disorders in the nervous system become more serious, they can lead to a complete paralysis. A university campus is to provide comfortable working conditions for scientists – preservers and generators of knowledge. Comfort is a special thing for them. The level of material needs among campus residents is usually not very high. Their food, clothing and housing requirements are rather modest. Certainly, the sense of security is necessary – any violation in the campus is very painful, like touching a naked nerve. But the most important and vital thing in the campus is a constant and intense flow of all kinds of information. The Internet, libraries, scientific conferences, symposiums and forums are necessary to the campus as the breath of life. It makes dying gasps without it. At the same time, all these “adventures of a thought” are outwardly almost undistinguished. Intensively thinking people look lazy and even inert. A true brainwork is not intension of the Thinker by Roden, but relaxation and meditative calm. (Isn’t it the reason why mental workers seem to be idlers in the eyes of administrators?...) In the Late Medieval and Renaissance eras, first universities adopted from monasteries the practice of creating the forms of life comfortable for the society’s “nervous system”. It is difficult to add something crucially new to this millenarian experience. Therefore, modern campuses (or modern elements of old campuses) are built on the same principles as in the 13th century. Cambridge, one of the oldest university complexes in Europe, can serve as a fine example of an effectively organized campus. Its image is less aristocratic and more applicable than the image of its eternal competitor – Oxford. But they are organized almost equally. Their financial and political independence protects them from economical fluctuations and governmental crises, like a skull protects brain from strokes and cold. The campuses’ interior is traditional, comfortable and calm. Their intellectual life is full of intense flows of new knowledge. What is the life like in the Cambridge campus? The article “On the English Land, on Another Planet… Interview with a resident of Cambridge” by Ekaterina Antipina contains an interview from the first person.